2006
DOI: 10.1139/x06-143
|View full text |Cite
|
Sign up to set email alerts
|

The spatial influence of Pseudotsuga menziesii retention trees on ectomycorrhiza diversity

Abstract: Living retention trees are being used in managed forests to promote a variety of values, including the maintenance of biological diversity. Federal forest plans for the northwestern USA include guidelines that require the retention of a minimum of 15% basal area in harvest units, with the goal of facilitating the development of late-seral stand structure, which is an important habitat element for old-growth forest-dependent species. However, effective levels and patterns of green-tree retention are unknown. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(22 citation statements)
references
References 48 publications
(60 reference statements)
2
20
0
Order By: Relevance
“…The community structure with regard to the abundance of ECM taxa was similar in all of the forest types examined, following the log-normal distribution similar to ECM communities in other coniferous (Horton and Bruns 2001;Kranabetter 2004;Luoma et al 2006;Cline et al 2005) and deciduous forests (Courty et al 2008). This distribution is due to the samples being dominated by a few ECM taxa with high abundances, with the remainder taxa present at low frequencies.…”
Section: Taxa Richnessmentioning
confidence: 55%
See 1 more Smart Citation
“…The community structure with regard to the abundance of ECM taxa was similar in all of the forest types examined, following the log-normal distribution similar to ECM communities in other coniferous (Horton and Bruns 2001;Kranabetter 2004;Luoma et al 2006;Cline et al 2005) and deciduous forests (Courty et al 2008). This distribution is due to the samples being dominated by a few ECM taxa with high abundances, with the remainder taxa present at low frequencies.…”
Section: Taxa Richnessmentioning
confidence: 55%
“…The final column lists the mean (and standard deviation) Jaccard value for each forest type conditions (Druebert et al 2009;Pena et al 2010). In the case of all three forest types, C. geophilum was found to be one of the most frequent ECM taxa, a finding common to many other ECM surveys in different forest types (Goodman and Trofymow 1998;Luoma et al 2006;Ishida et al 2007;Buee et al 2007;Pickles et al 2010;Lang et al 2011). ECM community analysis using below-ground data showed that each forest type had a statistically distinctive ECM community; this was because most ECM taxa recorded from a forest type were confined to that forest type, and relatively few taxa were shared between the three forest types.…”
Section: Taxa Richnessmentioning
confidence: 60%
“…Some studies investigating EM fungal species richness observed values at least twofold greater than those observed in this study. However, those studies were conducted on sites with higher ecological complexity and/or for a longer time period with moreintense sampling (35,45,46,54,55,69,75,81). Methodological considerations.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown, for example, that maintaining "nurse shrubs" on sites may maintain these species in situ (Kitzberger et al 2000). Retention of living trees can also provide refugia for mycorrhizal fungi; the number and size of retention patches is thought to be an important consideration for preservation of mycorrhizal diversity, with patch sizes of only about 10 m across providing significant benefit in some cases (Outerbridge and Trofymow 2004, Cline et al 2005, Luoma et al 2006, Jones et al 2008. Although the impacts of mycorrhizal diversity on productivity depend on site characteristics (Jonsson et al 2001), the distribution and size of migrated forest patches will likely be a consideration when establishing trees in new types of habitat.…”
Section: Mitigation Of Ecological Constraints At Different Scales Of mentioning
confidence: 99%